A New Institutional Perspective on Alternative Governance Mechanisms at the Local Government Level - Wallis, Joe; Dollery, Brian (Journal of Public Governance, 2010)
The “new institutional economics” (NIE) can go a long way toward comprehending the emerging complexities of local government. As local bodies seek to forge collaborative partnerships with other organizations, they have to decide whether to solve horizontal co-ordination problems through market, hierarchy or network mechanisms. NIE can show that where other governance mechanisms are incomplete or subject to high transaction costs, trust and cooperation can develop informally through the process by which network interactions become embedded within each other. We show how this approach can be revised to take into account the expressive dimension of behavior in hope-based networks whose members are bound together not so much by structures of resource dependence as by the hope they place in the advancement of common goals. To co-ordinate these networks in multi-organizational partnerships, local authorities may have to play a transformational leadership as well as a facilitative role.